Real-Time Distributed Data Aggregation in Edge Systems - Coelho, Nuno Gonçalo Sales Barreto Das Neves (2020)
We currently live in a world where everybody relies on smartphones and tablets to per- form their duties and daily actions. People now use these devices for just about anything, including surfing the web, reading e-mails, playing video games, or simply reading and writing documents. As a result of the mass adoption of mobile devices, the edges of the Internet have become resource-rich spaces with tons of devices that have their computa- tional power underutilized in many different ways. To expand the categories of novel applications currently being developed for the re- cently introduce hyper-local cloud-edge scenario, we propose a new category of applica- tions that require participating users to cooperate or collaborate among themselves, in order to achieve a common goal. To this end we propose Sage, a distributed middleware with a generic framework that is able to receive data from multiple sources, aggregate that data with defined algorithms and parameters, and send the aggregated result to the final application.